2017
DOI: 10.1016/j.chembiol.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Organoids as a Pre-clinical Cancer Model for Drug Discovery

Abstract: Tumor organoids are 3D cultures of cancer cells that can be derived on an individual patient basis with a high success rate. This creates opportunities to build large biobanks with relevant patient material that can be used to perform drug screens and facilitate drug development. The high take rate will also allow side-by-side comparison to evaluate the translational potential of this model system to the patient. These tumors-in-a-dish can be established for a variety of tumor types including colorectal, pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
340
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 419 publications
(343 citation statements)
references
References 62 publications
(125 reference statements)
0
340
0
3
Order By: Relevance
“…We next showed that tumor AOs can be used for drug screening (Weeber et al, 2017). As shown in Fig 3D, individual tumor AOs varied greatly in their respective responses in line with their mutational profile.…”
Section: Generation and Characterization Of Human Airway Organoidsmentioning
confidence: 82%
“…We next showed that tumor AOs can be used for drug screening (Weeber et al, 2017). As shown in Fig 3D, individual tumor AOs varied greatly in their respective responses in line with their mutational profile.…”
Section: Generation and Characterization Of Human Airway Organoidsmentioning
confidence: 82%
“…Furthermore, these patient-derived spheroids can be used to establish large and well-characterized biobanks that comprise the entire spectrum of molecular subtypes comprising the tumor and, subsequently, perform drug screens toward a more personalized and effective therapeutics (Pauli et al, 2017;Weeber, Ooft, Dijkstra, & Voest, 2017).…”
Section: Future Directionsmentioning
confidence: 99%
“…To study therapeutic models in cancer research, 3D organoid models of ductal pancreatic cancers have provided a new spectrum of models of tumor progression by forming neoplasms that proceed to form invasive and metastatic carcinomas [210]. The organoid methodology is a useful system that can be used to identify the characteristics of malignancy, and the creation of complete tissues or neoplastic cancer organoids in vitro might provide better models of cancers in the future [35, 211214]. Moreover, the CRISPR/Cas9 approach is believed to be a new breakthrough technology that can be used to correct cancer genomes for clinical applications [214].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The organoid methodology is a useful system that can be used to identify the characteristics of malignancy, and the creation of complete tissues or neoplastic cancer organoids in vitro might provide better models of cancers in the future [35, 211214]. Moreover, the CRISPR/Cas9 approach is believed to be a new breakthrough technology that can be used to correct cancer genomes for clinical applications [214]. However, Haapaniemi et al [212] and Ihry et al [213] demonstrated that CRISPR/Cas9 genome editing technology induces p53-mediated DNA damage and that, in human PSCs, p53 inhibits CRISPR/Cas9-induced genome editing.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%